The Influence of Financial Literacy, Budgetary Control, and Strategic Planning on Business Success of Startups in Indonesia - Mirda, SE. MM, DR. Hj Rizyana; Sari, SE., MM, Pipit Novila; Rimbano, Dheo (International Journal of Business, Law, and Education, 2024)
This study investigates the influence of financial literacy, budgetary control, and strategic planning on the business success of startups in Indonesia. Using a quantitative approach, data were collected from 150 startup founders through structured questionnaires, and multiple regression analysis was employed to assess the relationships between the variables. The results reveal that financial literacy, budgetary control, and strategic planning all have positive and significant impacts on business success, with strategic planning being the strongest predictor. The findings emphasize the critical role of financial management and strategic foresight in enhancing the growth and sustainability of startups. Practical implications include the need for increased financial education and support for strategic planning within the entrepreneurial ecosystem. Limitations and directions for future research are discussed